An approach to the synthesis of α,α,α - trisubstituted alkylhydrazine derivatives from carboxylic acids - Kokhan, S.O.; Tymtsunik, A.V.; Moskvina, V.S.; Grygorenko, O.O. (Reports of the National Academy of Sciences of Ukraine, 2020)
A preparative approach to the synthesis of alkylhydrazine derivatives with tertiary alkyl substituent at the nitrogen atom is proposed. It is based on the formal hydrazino-decarboxylation reaction of the corresponding α,α,α - trisubstituted carboxylic acids. The developed procedure does not require the use of expensive or hardly available metalo- or organocatalysts, as well as special equipment. The method is based on the radical photochemical decomposition of Barton esters (1-hydroxypyridine-2(1H)-thione esters, that can be easily synthesized from the carboxylic acids in two steps via the corresponding acyl chlorides) in the presence of di(tert-butyl) azodicarboxylate upon irradiation with a usual 500 W incandescent lamp. A plausible mechanism of this reaction includes the initial formation of tertiary alkyl and (2-pyridyl)thiyl radicals (as well as carbon dioxide) from the Barton ester. The tertiary alkyl radical then adds to the double N=N bond of azodicarboxylate to form the corresponding hydrazinyl radical, which then abstracts a hydrogen atom from some molecule present in the reaction mixture (typically, solvent) to give the target di-Boc-hydrazine. Hydrogen atom donor (that is, the solvent) has the key role for the successful outcome of this transformation. With too reactive hydrogen donors, the product of reductive decarboxylation is formed preferentially, whereas, with a hydrogen donors of low reactivity, the recombination of tertiary alkyl and (2-pyridyl)thiyl radicals becomes the major process. The best results are obtained, when the reaction is performed in chloroform. For most substrates (i.e. tert-butyl, 2,3-dimethylbut-2-yl, 1-methylcyclopent- 1-yl, 1-methylcyclobut-1-yl, 3-methyltetrahydrofuran-3-yl, and 2-metoxy-tert-butyl derivatives), the corresponding protected hydrazines are obtained with high yield (63–87 %). When the corresponding tertiary radical intermediates have moderate or low stability (adamant-1-yl, 1-methylcycloprop-1-yl, and 3-tertbutylbicyclo[ 1.1.1]pent-1-yl derivatives), the yields of the products are significantly diminished.